PEMIKIRAN CONFUCIUS DALAM KODE ETIK INDIVIDU SEBAGAI JALAN TENGAH DARI KRISIS IDENTITAS - Raihan Chaerani Putri Budiman (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2024)
Identity crisis is a problem that often occurs today. The issue of identity crisis occurs because humans do not understand their existence and lack self-confidence; besides that, identity crises occur based on several problems, namely academic, family and romance. The method used in this study is to use qualitative research methods with data obtained from library research. Confucius wrote many works. Confucian philosophy is a philosophy that has had a significant influence in China. The teachings of Confucius emphasize how to live a harmonious life by prioritizing morality or virtue and leading to the ideals of human beings as individuals and in society. The Individual Code of Ethics is the thought of the Chinese philosopher, namely Confucius. The Individual Code of Ethics is the characteristic that must be possessed, namely the concept of the ideal human being. In it, there are several characteristics that humans must have, namely Jen (humanity), Hao (respect for parents), Chun-tzu (gentlemen), and Li (etiquette), and what underlies these traits is that they must have the nature of Chih (Wisdom). Educating about the personal code of ethics and applying it to humans can be a middle way to overcoming an identity crisis because individuals can know themselves more deeply and know that there are values ??in themselves so that the identity crisis can be overcome.